Implementation of Information and Communication Technology Utilization in The Learning Process of Cadets in The Laboratory - Nugraha, I Made Aditya; Desnanjaya, I Gusti Made Ngurah (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
The role of ICT media in the teaching and learning process has grown rapidly since Covid-19 attacked all countries, including Indonesia. The implementation and development of ICT media can have a good impact considering that currently all aspects of life are connected to the internet. To be able to support learning activities in accordance with the Freedom of Learning Independent Campus policy, ICT media is implemented for learning in the laboratory. Methods of observation, mentoring and giving questionnaires are used in knowing the role of this media. 50 respondents took part in this learning activity from 2022-2023. Testing with the Spearman and Wilcoxon tests is also used to get an overview of the activities that have been carried out. Spearman test results show that there is a very strong correlation between available learning in terms of understanding, learning objectives, interest, and supporting the learning process. Meanwhile, the Wilcoxon test showed significant results between knowledge before and after participating in learning with ICT media with a p-value of 0.001.